Penerapan Teknik Scribble dalam Menggambar Bentuk Buah-Buahan Siswa Kelas VIII Sekolah Menengah Pertama - Lucky Tohuzisöchi Harefa; Anam Ibrahim (Mahesa Research Center, 2022)
The method used in this research is descriptive qualitative. The population in this study were several works by class VIII students of Bunga Mawar Gunungsitoli Private Junior High School with a total of five works and the research sample was several works by class VIII students, totaling five works using the Total Sampling technique. The results showed that the application of the scribble technique for drawing fruit shapes, grade VIII SMP Swasta Bunga Mawar Gunungsitoli on average got a very good category with a total of two works, got a good category a total of two works, while getting a poor category a total of one work. In the results of the recapitulation of the value of the fruit shape drawing with the scribble technique, the proportion indicator gets a good category with an average value of 77.3 and the dark and light indicator gets a good category with an average score of 78.98. Furthermore, the highest score on student work by getting an average score of 90 on work number two and the lowest score on student work with an average score of 58.3 on work number four. Based on the results of data analysis, it was concluded that the results of the drawing of the shape of the fruit with the scribble technique of the Bunga Mawar Gunungsitoli Private Junior High School could be said to be good.